Divergent effects of listening demands and evaluative threat on listening effort in online and laboratory settings - Carolan, Peter J.; Heinrich, Antje; Munro, Kevin J.; Millman, Rebecca E. (Frontiers in Psychology, 2024)
Objective Listening effort (LE) varies as a function of listening demands, motivation and resource availability, among other things. Motivation is posited to have a greater influence on listening effort under high, compared to low, listening demands. Methods To test this prediction, we manipulated the listening demands of a speech recognition task using tone vocoders to create moderate and high listening demand conditions. We manipulated motivation using evaluative threat, i.e., informing participants that they must reach a particular “score” for their results to be usable. Resource availability was assessed by means of working memory span and included as a fixed effects predictor. Outcome measures were indices of LE, including reaction times (RTs), self-rated work and self-rated tiredness, in addition to task performance (correct response rates). Given the recent popularity of online studies, we also wanted to examine the effect of experimental context (online vs. laboratory) on the efficacy of manipulations of listening demands and motivation. We carried out two highly similar experiments with two groups of 37 young adults, a laboratory experiment and an online experiment. To make listening demands comparable between the two studies, vocoder settings had to differ. All results were analysed using linear mixed models. Results Results showed that under laboratory conditions, listening demands affected all outcomes, with significantly lower correct response rates, slower RTs and greater self-rated work with higher listening demands. In the online study, listening demands only affected RTs. In addition, motivation affected self-rated work. Resource availability was only a significant predictor for RTs in the online study. Discussion These results show that the influence of motivation and listening demands on LE depends on the type of outcome measures used and the experimental context. It may also depend on the exact vocoder settings. A controlled laboratory settings and/or particular vocoder settings may be necessary to observe all expected effects of listening demands and motivation.